Advancing Energy Transition: Solar PV and Battery Energy Storage Integration in Indonesia–South Korea Cooperation - Abdul Khakim Mahfud ZUBAIDI; Isya Wiradisna FAIZAL (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study aims to analyze Indonesia’s energy transition by modeling the integration of solar PV and Battery Energy Storage Systems (BESS) while assessing the role of Indonesia–South Korea cooperation in enhancing technological adoption, investment, and energy diplomacy.Methodology:This research employs a multidisciplinary approach combining quantitative mathematical modeling of solar PV–BESS integration with qualitative analysis of Indonesia–South Korea cooperation through international political economy and energy diplomacy frameworks.Findings:The study finds that integrating solar PV with Battery Energy Storage Systems (BESS) could significantly enhance Indonesia’s grid reliability. Mathematical modeling shows that PV–BESS integration improves grid reliability and reduces coal reliance. reduce coal dependency, while Indonesia–South Korea cooperation provides technological, financial, and diplomatic leverage to accelerate the renewable energy transition.Implication:The findings imply that Indonesia should expand rooftop and utility-scale solar PV with BESS to secure the electricity supply, while hybrid systems can cut fuel costs in remote areas. Collaboration with South Korea can further accelerate deployment through technology transfer and local battery production.